Information without Implementation: A Practical Example for Developing a Best Practice Education Control Group. Issue 5 (2nd September 2016) - Balderson, Benjamin H.; McCurry, Susan M.; Vitiello, Michael V.; Shortreed, Susan M.; Rybarczyk, Bruce D.; Keefe, Francis J.; Korff, Michael Von
Abstract : This article considers methodology for developing an education-only control group and proposes a simple approach to designing rigorous and well-accepted control groups. This approach is demonstrated in a large randomized trial. The Lifestyles trial ( n = 367) compared three group interventions: (a) cognitive-behavioral treatment (CBT) for osteoarthritis pain, (b) CBT for osteoarthritis pain and insomnia, and (c) education-only control (EOC). EOC emulated the interventions excluding hypothesized treatment components and controlling for nonspecific treatment effects. Results showed this approach resulted in a control group that was highly credible and acceptable to patients. This approach can be an effective and practical guide for developing high-quality control groups in trials of behavioral interventions.